Brightness fluctuations of the Sun and p‐mode oscillations: The inverse problem and nonadiabatic waves in the photosphere. Issue 2 (February 2014) - Prokhorov, A.; Zhugzhda, Y.D.; Berdyugina, S.
Abstract Using photometric observations of the Sun as a star (DIFOS, SoHO) we were able to solve the inverse heloiseismic problem and determine the global time‐dependent relative temperature fluctuations as functions of the geometric height. This was done under the adiabatic assumption. A mathematical tool was developed to solve the inverse problem, which is ill‐posed. The calculations were done using the numerical software Matlab 7. The adiabatic solution shows signs of temperature waves in the lower photosphere, which agrees with calculations done by Rodríguez Hidalgo et al. (2001) and Stodilka (2011). (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)